Faktor Penghambat Penegakan Hukum Merek Di Sumatera Utara - Muhammad Citra Ramadhan; Rizkan Zulyadi; Siti Nur Khadijah; Jaya Prana Pinem (Universitas Medan Area, 2022)
This research was conducted in order to identify the factors that become obstacles in the enforcement of criminal law marks in the jurisdiction of the Regional Police of North Sumatra (Poldasu). The method used in this research is normative-empirical law research (applied law research). A literature study was conducted on the legal literature, a field study was conducted on respondents with in-depth interviews with 2 officers from the Criminal Investigation Unit at Poldasu. The results of the research and discussion show that law enforcement is influenced by several factors, which then become obstacles in the implementation of the process, such as: 1) Legal factors, where the term that refers to criminal marks in Law no. 21 of 2016 concerning Marks and Geographical Indications (UU MIG) uses the word “violation” and there are provisions for complaint offenses; (Constitution); 2) Law enforcement factors, namely the parties that form and apply the law; 3) Factors of facilities and facilities that support law enforcement; 4) Community factors, namely the environment in which the law applies and is applied. 5) Cultural factors, namely as a result of work, creativity and taste based on human initiative in social life